The Outcomes of Organizational Cronyism: A Social Exchange Theory Perspective - Ali, Shahab; Shahzad, Farrukh; Hussain, Iftikhar; Yongjian, Pu; Khan, Muhammad Mahroof; Iqbal, Zafar (Frontiers in Psychology, 2022)
The current research examines the possible outcomes of cronyism like organizational deviance (OD), organizational cynicism (OCy), and counterproductive work behavior and also investigates the mediating variable violation of psychological contract (VPC) among cronyism and its possible outcomes. Many studies have investigated the presence of organizational cronyism (OC) at the workplace and its impacts on certain variables. However, the outcomes observed in this study, i.e., OD, OCy, and counter-productive work behavior were not empirically investigated previously as per researchers’ knowledge. The second gap this study fills is the mediating effect of VPC between the studied variables. Thirdly, the study was conducted in Azad Jammu and Kashmir, Pakistan, which is almost the first attempt to investigate this phenomenon in Azad Jammu and Kashmir. Data were collected from the employees working under different ministries of Azad Jammu and Kashmir, Pakistan like education, forest, sports, information, local government, finance, and tourism. The data from 350 employees were collected through convenience sampling. The data collection process was conducted at two distinct time lags. Results show that OC significantly and positively relates with OD, OCy, and counter-productive work behavior, whereas VPC mediates the relationship among OC and OD, OC, and counter-productive work behavior. Employees enjoying special favors from the leadership seem to be more dedicated toward the organization than the employees who do not have this favor, and the ultimate result is negative for the organization.